A ganglion cyst that developed from the infrapatellar fat pad of the knee - art. no. E14 - Yilmaz, E; Karakurt, L; Özercan, I; Özdemir, H (W B Saunders Co-Elsevier Inc, 2004)
A ganglion cyst may be seen in all joints with varying frequency depending on location, but it is rare in the knee joint. A 30-year-old man presented with a mass in the anterolateral aspect of his left knee. Magnetic resonance imaging revealed an intra-articular tumor arising from the infrapatellar fat pad of the knee. This multilobular tumor showed low signal intensity on T1-weighted images and high signal intensity on T2-weighted images. Complete open resection was performed after arthroscopic examination. Histologic examination of the specimen confirmed the diagnosis of ganglion cyst. At the 1-year follow-up examination, the patient's left knee was completely asymptomatic with full range of motion and no recurrence. Ganglion cyst should be considered in the differential diagnosis of intra-articular masses.
Keywords: ganglion cyst; knee joint; arthroscopy; infrapatellar fat pad